Development of a coupled numerical model for the interaction between transient fluid slosh and tank wagon vibration. (September 2019) - Rahmati-Alaei, Ahmad; Sharavi, Majid; Samadian Zakaria, Masoud
In this paper, a coupled model is developed to evaluate the effect of transient fluid slosh on the railway tank wagon dynamic vice versa. This model has computational complexity in solving the Navier–Stokes equations and nonlinear differential equations of tank wagon vibration with nonlinear wheel–rail contact. The coupled model can be used as an effective and robust tool compared to simplified models for assessing the stability of tank wagon. The transient fluid slosh model is analysed using the computational fluid dynamic method combined with the volume of fluid technique. The tank wagon dynamic model is solved using the fourth-order Runge–Kutta method based on the 19 degrees of freedom model with longitudinal, vertical, roll and pitch vibrations. The wheel–rail contact is considered according to nonlinear Hertzian and Kalker linear rolling contact theories. The fluid slosh model is validated using experimental data. The dynamic response characteristics of the partially filled railway tank wagon are investigated under straight-line braking manoeuvre using the coupled model. The results obtained from a parametric study, including the cross sectional shape and the filled volume show that the modified-oval cross section improves the dynamic response characteristics, which are attributed to its lower fluid's centre of gravity coordinate in the longitudinal direction and low lateral moment transfer of the fluid.